Kata Bermakna Laki-Laki Pada Teks Terjemahan Alquran - Yunitasari, Ana Putri, Prof. Dr. Hj. Markhamah. M.Hum (2016)
This study has the objective to identify the forms of words that are men synonymy relations, hiponimy, and antonym to the text translation of the Qur'an (Surah Al Baqarah, Al, An-Nisa, and Al Ma'idah). This type of research is qualitative descriptive. This study was content analysis. The data in this study is a meaningful word men in text translations of the Qur'an. Source of the data contained in this study is a sentence that included a meaningful words of men. In collecting the data, this study using techniques refer to note that the form of written text translations of the Qur'an. Mechanical log an advanced technique.Data analysis techniques in this study is a technique for the direct element (BUL). Use sequel technique used is the technique of expanding. The results of the analysis, (1) the form of words used in expressing meaningful words male text translations of the Qur'an, among others, (a) personal pronouns (13 words), (b) a noun phrase (11 phrases), (c) noun (11 words ), (d) the name of the self (20 names). (2) Relationship synonymy, hiponimi and antonym are: (a) synonyms meaningful words of men (14 names), (b) hyponymy and hypernymy meaningful words of men (personal pronoun first (4 names), personal pronouns second (5 names ), the third personal pronouns (3 names), (persona name themselves (20 names), (persona self-nam (11 names), (c) antonyms meaningful words of men (5 names).